Fundamentals of sustainability in civil engineering. - Braham, Andrew (Boca Raton : CRC Press, 2020)
This book provides a foundation to understand the development of sustainability in civil engineering, and tools to address the three pillars of sustainability: economics, environment, and society. It includes case studies in the five major areas of civil engineering: environmental, structural, geotechnical, transportation, and construction management. This second edition is updated throughout and adds new chapters on construction engineering as well as an overview of the most common certification programs that revolve around environmental sustainability. Features: Updated throughout and adds two entirely new chapters Presents a review of the most common certification programs in sustainability Offers a blend of numerical and writing-based problems, as well as numerous application-based examples that utilize concepts found on the Fundamentals of Engineering (FE) exam Includes several practical case studies Offers a solution manual for instructors Fundamentals of Sustainability in Civil Engineering is intended for upper-level civil engineering sustainability courses. A unique feature is that concepts found in the Fundamentals of Engineering (FE) exam were targeted to help senior-level students refresh and prepare.
Previous edition: 2017.
OCLC-licensed vendor bibliographic record.
Keywords: Civil engineering; Sustainable engineering; TECHNOLOGY / Construction / General; TECHNOLOGY / Environmental Engineering & Technology; SCIENCE / Environmental Science